Analytical methods for analysing adherence to drug theraphy at individual patient level using Malaysian electronic health record - Zin, Che Suraya
This analytical method is used to characterise adherence to drug therapy at the individual patient level suing the Malaysian electronic health records. This method allows advanced analysis to be conducted that can improve patient outcomes at the patient level. The existing available method is for aggregated level which merely provides a statistical report at the organization level and is unable to improve patient outcomes. The individual patient level method is new to the Malaysian healthcare database and copyright should be filed,